1986
DOI: 10.1111/j.1365-2125.1986.tb05188.x
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular effects of xamoterol, a beta 1‐adrenoceptor partial agonist, in healthy volunteers at rest.

Abstract: School, Minamikawachi-machi, Tochigi Prefecture, Japan 1 The cardiovascular effects of three single intravenous doses of a Pl-adrenoceptor partial agonist, xamoterol (0.025, 0.05 and 0.1 mg kg-') and placebo were studied in six healthy volunteers at rest using a single-blind design. 2 In addition to heart rate and blood pressure measurements, cardiac contractility was measured by means of M-mode echocardiography and systolic time intervals. Ambulatory 24 h Holter-monitoring of the electrocardiogram was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…By contrast, oxprenolol has modest activity and xamoterol, a newer j1-selective adrenoceptor agent, possesses high ISA. In the dog the latter has been shown to possess 43% of the full agonist activity of isoprenaline on heart rate (Nuttall & Snow, 1982); in other animal species (Malta etal., 1985) and in man (Hashimoto et al, 1986) phase (1 session) five of the subjects (the sixth was not available to take part) knowingly took: metoprolol 100 mg in order to verify that the changes already observed with atenolol were not unique to that drug.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, oxprenolol has modest activity and xamoterol, a newer j1-selective adrenoceptor agent, possesses high ISA. In the dog the latter has been shown to possess 43% of the full agonist activity of isoprenaline on heart rate (Nuttall & Snow, 1982); in other animal species (Malta etal., 1985) and in man (Hashimoto et al, 1986) phase (1 session) five of the subjects (the sixth was not available to take part) knowingly took: metoprolol 100 mg in order to verify that the changes already observed with atenolol were not unique to that drug.…”
Section: Introductionmentioning
confidence: 99%
“…In some animal models and normal healthy volunteers, it produces approximately 43% of the maximum response of the full agonist isoprenaline (Nuttall & Snow, 1982;Hashimoto et al, 1986). The modest inotropic action of this drug is associated with a beneficial effect on stabilising sympathetic stimulation of the heart, providing inotropic support at low levels of sympathetic drive and protection from excessive and potentially metabolically harmful stimulation during exertion.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…no peripheral vasodilating effects in doses producing significant positive inotropism (Nuttall & Snow, 1982). In normal volunteers and heart failure patients it has a 'stabilising' action on sympathetic drive producing little or no effect on resting heart rate whilst inhibiting rapid exercise induced tachycardia (Hashimoto et al, 1986;Sato et al, 1987). Xamoterol has positive inotropic effects in normal volunteers (Hashimoto et al, 1986) and positive inotropic and lusitropic effects have been demonstrated in patients with ischaemic heart failure (Pouleur et al, 1982(Pouleur et al, , 1986.…”
Section: -Adrenoceptor Partial Agonistsmentioning
confidence: 99%
“…In normal volunteers and heart failure patients it has a 'stabilising' action on sympathetic drive producing little or no effect on resting heart rate whilst inhibiting rapid exercise induced tachycardia (Hashimoto et al, 1986;Sato et al, 1987). Xamoterol has positive inotropic effects in normal volunteers (Hashimoto et al, 1986) and positive inotropic and lusitropic effects have been demonstrated in patients with ischaemic heart failure (Pouleur et al, 1982(Pouleur et al, , 1986. In a similar group of patients acute intravenous administration of xamoterol did not modify myocardial oxygen consumption or lactate extraction despite a positive inotropic effect .…”
Section: -Adrenoceptor Partial Agonistsmentioning
confidence: 99%